2019
DOI: 10.2147/jaa.s205482
|View full text |Cite
|
Sign up to set email alerts
|

<p>Detection of pepsin and IL-8 in saliva of adult asthmatic patients</p>

Abstract: Objective: Asthma and gastric reflux disease are widespread and often coexisting diseases with complex interactions, leading some to suspect that asthma symptoms of patients with reflux may improve with anti-reflux therapy. The objective of this study was to determine whether pepsin in saliva, indicative of airway reflux, could be detected in patients with asthma of varying severity and test the requirement of citric acid as a pepsin preservative. Methods: Saliva samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…The current survey reveals similar lack of awareness of the potential role of LPR in development of laryngotracheal stenosis and chronic media otitis, despite an increasing literature which supports this relationship. 10,11,26,27 Surprisingly, non-laryngologists seem to be unaware about the role of LPR in bronchial diseases such as asthma; however, many studies have demonstrated that LPR is involved in the development of bronchial hypersensitivity conditions, such as asthma, 28,29 or chronic obstructive pulmonary disease. 30 In the current survey, the largest differences between laryngologists and non-laryngologists concern diagnostic approach towards LPR, particularly with regard to examinations such as esophagoscopy and MII-pH.…”
Section: Discussionmentioning
confidence: 99%
“…The current survey reveals similar lack of awareness of the potential role of LPR in development of laryngotracheal stenosis and chronic media otitis, despite an increasing literature which supports this relationship. 10,11,26,27 Surprisingly, non-laryngologists seem to be unaware about the role of LPR in bronchial diseases such as asthma; however, many studies have demonstrated that LPR is involved in the development of bronchial hypersensitivity conditions, such as asthma, 28,29 or chronic obstructive pulmonary disease. 30 In the current survey, the largest differences between laryngologists and non-laryngologists concern diagnostic approach towards LPR, particularly with regard to examinations such as esophagoscopy and MII-pH.…”
Section: Discussionmentioning
confidence: 99%
“…До последнего времени исследования, обосновывающие возможность считать пепсин суррогатным биомаркером ГЭРБ, не остаются без внимания научного сообщества [30,57]. Однако в некоторых работах не было выявлено существенной связи между значениями пепсина слюны и тяжестью клинических проявлений БА [41,58]. Более того, в исследовании Race С. et al было показано, что слюнный пепсин не является надежным инструментом для диагностики ГЭРБ [59].…”
Section: биомаркеры гастроэзофагеального и дуоденогастроэзофагеальног...unclassified
“…On the other hand, a study by Marshall et al performed on 25 asthmatic patients showed no significant correlation between salivary pepsin levels and clinical measures of asthma severity [ 26 ]. However, one of the major drawbacks of salivary pepsin assessment is the current lack of an optimal timeframe for sample collection.…”
Section: Pepsin Detection In Bronchial Asthmamentioning
confidence: 99%